Bukti Acara Pemeriksaaan Kepolisian sebagai Data Sejarah : Upaya Merekontruksi Kekerasan Banyuwangi Tahun 1998-1999: Evidence of Police Investigation Events as Historical Data: Efforts to Reconstruct the Banyuwangi Violence in 1998-1999 - Kusairi, Latif (Journal of Islamic History, 2021)
Writing a history of violence often encounters obstacles in finding data. This is due to the concern and silence of the perpetrators to reveal the chronology of historical events. The process of searching for archived data is sometimes also not found in archival institutions. In the other hand, historians are not yet very familiar with the data obtained from the authorities. The history of violence reconstruction with the issue of dukun santet in Banyuwangi is also the same. Investigation the data found many obstacles such as historical actors who do not want to tell incidents that happened. The role of the police archives and the court is very important, because in the minutes of the examination and the news of the court has been written. Historians need to view the archives of the court as an alternative when historians have difficulties in finding the data. At this point historians must be able to pick up archives not only fixated on archival institutions, but can look for the archives through institutions such as courts to see the chronology of violence that has occurred and has been tried in judicial institutions. Historians can go further for data analysis and can see the results of interviews conducted by the judiciary. This study will discuss the role of historians in seeking data from the court as a primary source.